THE ROLE OF FISCAL POLICY IN ENSURING THE STABILITY OF THE STATE BUDGET AND ITS FORMATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the role of fiscal policy and its main mechanisms in ensuring the stability of the state budget. It examines solutions to issues such as optimizing tax revenues, rationalizing expenditures, budget deficits, and debt burden. Based on Uzbekistan’s experience in fiscal policy, the article presents proposals for effective budget management.